The Contribution of Psychological well-being and Self-compassion toward Student’s Academic hardiness: A Study in Islamic Boarding School - Prabawa, Abi Fa'izzarahman (Universitas Negeri Semarang, 2023)
Islamic Boarding School is now an option for students who want to strengthen their religious knowledge and social skills. Students who live in Islamic boarding schools have more demands than students in general. Students must have academic hardiness in completing their studies, characterized by commitment, control, and challenge. Academic hardiness needs to be supported by psychological well-being and self-compassion. Psychological well-being helps students accept conditions and be able to control conditions well. Self-compassion helps students understand their situation so that they can face challenges. This study aims to analyze the contribution of psychological well-being and self-compassion to the academic hardiness of students in Islamic boarding schools. Quantitative research method with correlational design and samples were taken with convenience random sampling technique. The research instruments involved well-being, self-compassion, and academic hardiness scales. Data analysis used descriptive statistics and multiple linear regression tests. The results showed that psychological well-being and self-compassion had a significant effect of 61.5% (R2: 0.615) on the academic hardiness of students in the cottage. Other variables influence the remaining 38.5%. Thus, psychological well-being and self-compassion are essential in shaping islamic boarding school students' academic hardiness.